폴리이미드 종류에 따른 연성 동박 적층판의 부착력 연구 - 이재원(Jae Won Lee); 김상호(Sang Ho Kim) (Biuletyn Uniejowski, 2005)
Flexible copper clad laminates (FCCL) fabricated by sputtering has advantages in fine pitch etching and dimensional accuracy than previous casting or laminating type FCCL, But its lower adhesion is inevitable technical challenge to solve for commercializing it. Chromium (Cr) which strongly reacts with O moiety was used as tie-coating layer in order to improve low adhesion between copper (Cu) and polyimide (PI). Sputtering raw polyimide (SRPI) and casting raw polyimide (CRPI) were used as substrates at this research. PI was pretreated by plasma before sputtering, and each sample was varied with RF power and Cr thickness on sputtering. Peel strength of the FCCL on SRPI was higher than that on CRPI. Adhesion had maximum value when 10 nm of Cr was deposited on SRPI by RF power of 50 W. It seems to be by the formation of Cu-Cr-O solid solution at the metal-PI interface.